The Impact of Electrolyte Composition on Parasitic Reactions in Lithium Ion Cells Charged to 4.7 V Determined Using Isothermal Microcalorimetry. Issue 2 (1st January 2016) - Downie, L. E.; Hyatt, S. R.; Dahn, J. R.
Abstract : In an effort to better the understanding of the high voltage degradation of electrolytes in lithium ion cells, this work presents isothermal microcalorimetry results on LiNi0.42 Mn0.42 Co0.16 O2 (NMC442)/graphite pouch cells up to 4.7 V. The voltage and time dependent parasitic heat flow was determined for cells containing several electrolyte compositions based on carbonate solvents with several additive combinations, as well as a fluorinated carbonate solvent system. We have demonstrated that cells containing fluorinated carbonate-based electrolyte (1M LiPF6 in 3:7 fluoroethylene carbonate: di-2, 2, 2-trifluoroethyl carbonate) showed a significantly decreased parasitic heat flow at voltages >4.4 V compared to ethylene carbonate-based cells, but limited advantage <4.4 V. However all cells, regardless of electrolyte composition, exhibited very large parasitic heat flows, and therefore parasitic reaction rates, at high voltages (>4.35 V). The results presented here also show that high voltage (>4.5 V) cycling results in an increase in parasitic heat flow of the subsequent lower voltage cycles, and is indicative of a change in the dominant reaction pathway.